2019
DOI: 10.1016/j.joca.2019.02.358
|View full text |Cite
|
Sign up to set email alerts
|

Global oa management begins with quality of life assessment in knee oa patients: a systematic review

Abstract: Purpose: Globally, osteoarthritis (OA) is the third most rapidly rising condition associated with disability. Science holds the key to finding better treatments and one day a cure. Still it is essential we learn what's important to patients from the patients themselves in order to optimize implementation of better healthcare options for most effective global management of OA. Integrated people-centred health services, as defined by the World Health Organization, implies putting the comprehensive needs of peopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…This study was coordinated by patient organizations and previously promoted at the 2019 OARSI Annual Meeting advocating for routine assessment and on-going evaluation of QoL with implementation of a single agreed upon QoL measure [78]. Future KOA QoL research should combine efforts globally and focus on consistent quantitative and qualitative measures for more meaningful impact and interpretation.…”
Section: Resultsmentioning
confidence: 99%
“…This study was coordinated by patient organizations and previously promoted at the 2019 OARSI Annual Meeting advocating for routine assessment and on-going evaluation of QoL with implementation of a single agreed upon QoL measure [78]. Future KOA QoL research should combine efforts globally and focus on consistent quantitative and qualitative measures for more meaningful impact and interpretation.…”
Section: Resultsmentioning
confidence: 99%
“…As previously described, anxiety is associated with worse pain and physical function trajectories ( 51 ). Moreover, previous research indicates that education is an important social determinant for several chronic diseases, including OA, and is related to lifestyle factors, a lack of preventive measures, low access to healthcare services, and low literacy levels ( 42 , 52 ). Psychosocial variables such as a low level of self-efficacy, catastrophising, and pain sensitisation are also associated with poorer clinical outcomes ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found the age group >60 years old had the highest prevalence of knee OA (41.2%) with male to female ratio 1:1.8. Similar studies reported most knee OA patients were female [5,6,8,10] with the age more than 60 years [5,9,10]. Maharani EP et al reported female gender was one of the risk factors for OA (OR 2.14, p=0.043) [11].…”
Section: Discussionmentioning
confidence: 67%
“…The prevalence of OA is quite high among the elderly as stated from the American College of Rheumatology (ACR) 1986 clinical diagnosis criteria which is age over 50 years. Knee OA has negative impact on Quality of life [5,6]. The EQ-5D instruments have been shown to be valid and reliable instruments for evaluating Quality of life in patients with knee OA [7].…”
Section: Discussionmentioning
confidence: 99%